ЕЛЕКТРОМАГНІТНІ МОМЕНТИ УПРАВЛІННЯ ПРЕЦЕСІЙНИМ РУХОМ ТРИСТУПЕНЕВОЇ ЕЛЕКТРИЧНОЇ МАШИНИ - Петухов, І.С. (Інститут електродинаміки НАН України, Київ, 2023)
The main known structures and principles of functioning of electric machines with three degrees of freedom of rotational motion of the rotor are considered. The type of such machines in which it is possible to realize a high frequency of the rotor rotation is highlighted, which gives it the property of gyro-stabilization. The structure of the magnetic system of the machine of this type is presented and a hypothesis is put forward about the adequacy of the expressions of the classical analytical mathematical model, but the need for accurate calculation of the concentrated parameters that make up it. The distribution of magnetic flux density is analyzed based on a numerical mathematical model of a three-dimensional magnetic field. The dependences of electromagnetic torque components and flux linkages on the rotor axis orientation and the angle of its rotation are calculated. It was concluded that the classical analytical mathematical model are adequate provided that the calculating of its coefficients is based on the results of the modeling of three-dimensional magnetic field in the machine active volume and the surrounding space. It is underlined that, the amplitude of the flux linkage vector of the control winding and the fluctuations of the vector components to use in lumped parameter model must be calculated from the corresponding values of the electromagnetic torque components. Taking into account the results of the analysis of the three-dimensional field demonstrates a significant decrease in the speed of controlled precession and an increase in the amplitude of nutation. References 9, figures 10, tables 2.